A stable open-shell peri-hexacene with remarkable diradical character - Jinji Zhang; Xiaojing Fang; Weiwei Niu; Yiming Yu; Yanlin Hu; Jiawen Sun; Ying Xu; Zhihua Zhou; Heyuan Liu; Xiaonan Fan; Baishu Zheng; Qing Jiang; et al. (Nature Communications)
Abstract [n]Peri-acenes ([n]PA) have attracted great interest as promising candidates for nanoelectronics and spintronics. However, the synthesis of large [n]PA (n > 4) is extremely challenging due to their intrinsic open-shell radical character and high reactivity. Herein, we report the successful synthesis and isolation of a derivative (1) of peri-hexacene in crystalline form. The structure of 1 is unequivocally confirmed by X-ray crystallographic analysis. Its ground state, aromaticity and photophysical properties are systematically studied by both experimental methods and theoretical calculations. Although the parent peri-hexacene is calculated to have a very large diradical character (y 0 = 94.5%), 1 shows reasonable stability (t 1/2 = 24 h under ambient conditions) due to the kinetic blocking. 1 exhibits an open-shell singlet ground state with a small singlet-triplet energy gap (−1.33 kcal/mol from SQUID measurements). 1 has also a narrow HOMO-LUMO energy gap (1.05 eV) and displays amphoteric redox behavior. This work opens new avenues for the design and synthesis of stable zigzag-edged graphene-like molecules with significant diradical character.